Sovereignty and superheroes - Curtis, Neal (Manchester University Press, 2016)
This title marks a major contribution to the emerging field of comic studies and the growing literature on superheroes. Using a range of critical theorists, the book examines superheroes as sovereigns, addressing amongst other things the complex treatment of law and violence, legitimacy, and authority.